Experimental investigation on the solidification rate of water in open-cell metal foam with copper fins. (October 2018) - Bai, Qingsong; Guo, Zengxu; Cui, Xin; Yang, Xiaohu; Yanhua, Liu; Jin, Liwen; Sun, Yanjun
Abstract: This study focused on the effect of inserting fins into metal foam on the solidification rate. To this aim, a well-designed experimental system with solid-liquid interface visualization was built. Metal foam samples with different fin intervals were prepared for experiments. Solidification process of water saturating in finned metal foam under bottom cooling was experimentally investigated. Results showed that inserting fins into metal foam can make a promotional improvement on solidification rate of water. The solid-liquid interface became curved after inserting fins, compared with metal foam sample without fins. Besides, changing the interval has little effect on the solidification rate.